Integration of task-attribute based access control model for mobile workflow authorization and management - Basnet, Rejina, author; Ray, Indrakshi, advisor; Abdunabi, Ramadan, advisor; Ray, Indrajit, committee member; Vijayasarathy, Leo R., committee member (Colorado State University. Libraries, 2019)
Workflow is the automation of process logistics for managing simple every day to complex multi-user tasks. By defining a workflow with proper constraints, an organization can improve its efficiency, responsiveness, profitability, and security. In addition, mobile technology and cloud computing has enabled wireless data transmission, receipt and allows the workflows to be executed at any time and from any place. At the same time, security concerns arise because unauthorized users may get access to sensitive data or services from lost or stolen nomadic devices. Additionally, some tasks and information associated are location and time sensitive in nature. These security and usability challenges demand the employment of access control in a mobile workflow system to express fine-grained authorization rules for actors to perform tasks on-site and at certain time intervals. For example, if an individual is assigned a task to survey certain location, it is crucial that the individual is present in the very location while entering the data and all the data entered remotely is safe and secure. In this work, we formally defined an authorization model for mobile workflows. The authorization model was based on the NIST(Next Generation Access Control) where user attributes, resources attributes, and environment attributes decide who has access to what resources. In our model, we introduced the concept of spatio temporal zone attribute that captures the time and location as to when and where tasks could be executed. The model also captured the relationships between the various components and identified how they were dependent on time and location. It captured separation of duty constraints that prevented an authorized user from executing conflicting tasks and dependency of task constraints which imposed further restrictions on who could execute the tasks. The model was dynamic and allowed the access control configuration to change through obligations. The model had various constraints that may conflict with each other or introduce inconsistencies. Towards this end, we simulated the model using Timed Colored Petri Nets (TCPN) and ran queries to ensure the integrity of the model. The access control information was stored in the Neo4j graph database. We demonstrated the feasibility and usefulness of this method through performance analysis. Overall, we tended to explore and verify the necessity of access control for security as well as management of workflows. This work resulted in the development of secure, accountable, transparent, efficient, and usable workflows that could be deployed by enterprises.
Keywords: attribute based access control; TCPN analysis; workflow security; policy machine; access control; workflow management